Sulfide solid electrolyte and preparation method thereof, all-solid-state battery and electric equipment

By adopting core-shell structure and layer-by-layer doping elements in the sulfide solid electrolyte, the problems of its air instability and reduced conductivity are solved, and the electrochemical performance of all-solid-state batteries is improved and the assembly convenience of all-solid-state batteries is achieved.

CN119306191APending Publication Date: 2025-01-14ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411395022.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The sulfide solid electrolyte is unstable in the air and is easy to react with H2O in the air, resulting in structural damage and a decrease in ionic conductivity. The existing modification technology cannot effectively improve its air stability and reduce ionic conductivity, which limits its entirety. Applications in solid-state batteries.

Method used

The sulfide solid electrolyte with a core-shell structure has the same crystal structure. The molar amount of doped elements increases layer by layer, and the total molar amount of phosphorus and sulfur decreases layer by layer. Through multi-step mixing and Preparation of sintering method to ensure that the conductivity does not decrease while improving air stability.

Benefits of technology

The air stability and electrochemical properties of sulfide solid electrolytes are significantly improved, the need to assemble all-solid state batteries in a protective atmosphere is avoided, and the preparation and application costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073531600000101
    Figure BDA0005073531600000101
  • Figure BDA0005073531600000111
    Figure BDA0005073531600000111
  • Figure BDA0005073531600000121
    Figure BDA0005073531600000121
Patent Text Reader

Abstract

The invention relates to a sulfide solid-state electrolyte and a preparation method thereof, an all-solid-state battery and electric equipment, the sulfide solid-state electrolyte comprises an inner core and N shell layers sequentially coating the surface of the inner core, N is an integer greater than or equal to 2, the inner core and the shell layers are sulfide solid-state electrolytes doped with doping elements, the crystal structures of the inner core and the shell layers are the same, the inner core is used as the innermost layer, and in the direction from the innermost layer to the Nth shell layer, the molar weight of the doped element is increased layer by layer, and the total molar weight of the phosphorus element and the sulfur element is reduced layer by layer. The ionic conductivity of the sulfide solid electrolyte cannot be reduced, the air stability of the sulfide solid electrolyte can be remarkably improved, the electrochemical performance of an all-solid-state battery can be remarkably improved when the sulfide solid electrolyte is used for assembling the all-solid-state battery, and the service life of the all-solid-state battery is prolonged. And the all-solid-state battery does not need to be assembled in a protective atmosphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a sulfide solid electrolyte and a preparation method thereof, an all-solid-state battery and electrical equipment. Background Art

[0002] Compared with traditional liquid lithium-ion batteries, all-solid-state batteries using inorganic solid electrolytes not only provide a wider operating temperature range, but also have higher safety and energy density.

[0003] Among them, sulfide solid electrolytes have excellent ionic conductivity and mechanical properties and are commonly used inorganic solid electrolytes for all-solid-state batteries. However, sulfide solid electrolytes are unstable in the air and easily react with H2O in the air to release toxic and harmful gases H2S, causing structural damage, resulting in a sharp drop in ionic conductivity. In response to this, sulfide solid electrolytes are generally modified by bulk doping or surface coating. However, the existing modification technology not only does not significantly improve the air stability of sulfide solid electrolytes, but also causes a significant decrease in the ionic conductivity of sulfide solid electrolytes. Therefore, the synthesis of sulfide solid electrolytes and the assembly of all-solid-state batteries need to be carried out in a protective atmosphere, resulting in an increase in their preparation and application costs, hindering their application and development in all-solid-state batteries. Summary of the invention

[0004] Based on this, it is necessary to provide a sulfide solid electrolyte and its preparation method, an all-solid-state battery and electrical equipment to address the above problems, which will not only not reduce the ionic conductivity of the sulfide solid electrolyte, but also significantly improve the air stability of the sulfide solid electrolyte. When it is used to assemble an all-solid-state battery, the electrochemical performance of the all-solid-state battery can be significantly improved.

[0005] A sulfide solid electrolyte, comprising a core and N shell layers sequentially coated on the surface of the core, N being an integer greater than or equal to 2, the core and the shell layers being sulfide solid electrolytes doped with doping elements, wherein the core and the shell layers have the same crystal structure, and with the core as the innermost layer, in a direction from the innermost layer to the Nth shell layer, the molar amount of the doping element increases layer by layer, and the total molar amount of phosphorus and sulfur decreases layer by layer.

[0006] In one embodiment, the sulfide solid electrolyte also satisfies at least one of the following conditions:

[0007] (1) The molar amount of any doping element in the core is 0 to 0.01, and the molar amount of any doping element in the Nth shell is 0.003 to 0.25;

[0008] (2) In the direction from the innermost layer to the Nth shell, the mass of the outer layer in two adjacent layers is less than or equal to the mass of the inner layer.

[0009] In one embodiment, the sulfide solid electrolyte also satisfies at least one of the following conditions:

[0010] (1) From the innermost layer to the Nth shell layer, the difference in the total molar amount of the doping elements in two adjacent layers is 0.001 to 0.25;

[0011] (2) In the direction from the innermost layer to the Nth shell, the mass ratio of the outer layer to the inner layer in two adjacent layers is 1:1 to 0.1:1.

[0012] In one embodiment, the doping element is selected from at least one of B, O, Sb, Sn, Bi, Se, Zn, Fe, Cu, Ga, Zr, Y, Ta, W, In, Mo, Al, and N.

[0013] In one embodiment, the doping element is selected from at least one of O, Sb, Sn, Bi, Se, In, and N.

[0014] In one embodiment, N is 4, and the sulfide solid electrolyte includes an inner core and a first shell layer, a second shell layer, a third shell layer and a fourth shell layer sequentially coated on the surface of the inner core.

[0015] In one embodiment, the sulfide solid electrolyte satisfies at least one of the following conditions:

[0016] (1) The molar amount of the doping element in the core is a, 0≤a<0.01, the molar amount of the doping element in the first shell is b, 0.01≤b<0.03, the molar amount of the doping element in the second shell is c, 0.03≤c<0.05, the molar amount of the doping element in the third shell is d, 0.05≤d<0.1, and the molar amount of the doping element in the fourth shell is e, 0.1≤e<0.25;

[0017] (2) In the sulfide solid electrolyte, the mass fraction of the core is 50% to 70%, the mass fraction of the first shell is 10% to 30%, the mass fraction of the second shell is 5% to 15%, the mass fraction of the third shell is 3% to 10%, and the mass fraction of the fourth shell is 1% to 5%.

[0018] A method for preparing the sulfide solid electrolyte comprises the following steps:

[0019] In a protective atmosphere, the raw materials are mixed and sintered by dry mixing or wet mixing according to the composition of the core to obtain the core;

[0020] In a protective atmosphere, raw materials are added in sequence according to the composition and quantity of the shell layers, and mixing and sintering are continued to obtain a sulfide solid electrolyte.

[0021] An all-solid-state battery, wherein the all-solid-state battery uses the sulfide solid electrolyte.

[0022] An electrical device using the all-solid-state battery.

[0023] In the sulfide solid electrolyte of the present invention, the core and the shell have the same crystal structure, and the molar concentration of the doping element increases layer by layer from the innermost layer to the Nth shell layer. This doping modification method not only does not reduce the ionic conductivity of the sulfide solid electrolyte, but also can significantly improve the air stability of the sulfide solid electrolyte. Therefore, the use of the sulfide solid electrolyte of the present invention to assemble an all-solid-state battery can significantly improve the electrochemical performance of the all-solid-state battery, and the assembly of the all-solid-state battery does not need to be carried out in a protective atmosphere. DETAILED DESCRIPTION

[0024] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0026] The sulfide solid electrolyte provided by the present invention is a core-shell structure, including a core and N shells sequentially coated on the surface of the core, N is an integer greater than or equal to 2, for example, N is 2, 3, 4, 5, 6, 7, 8, etc. Wherein, the core and the shell are sulfide solid electrolytes doped with doping elements, and the doping elements are used to replace the phosphorus and sulfur elements in the sulfide solid electrolyte to improve the air stability of the sulfide solid electrolyte. Optionally, the doping element is selected from at least one of B, O, Sb, Sn, Bi, Se, Zn, Fe, Cu, Ga, Zr, Y, Ta, W, In, Mo, Al, and N, and is further preferably selected from at least one of O, Sb, Sn, Bi, Se, In, and N, which has a better effect of improving air stability.

[0027] It should be noted that the present invention does not limit the selection of the sulfide solid electrolyte. For example, the sulfide solid electrolyte is Li x MP y S z , M is one or more of Sn, Ge, Si, 0<x, 0<y, 0<z, or the sulfide solid electrolyte is Li 7-x-y PS 6-x-y Cl x X y , X is at least one of the halogen elements F, Br and I, 0≤x, 0≤y, or the sulfide solid electrolyte is xLi2S·(100-x)P2S5, 70≤x≤80, or the sulfide solid electrolyte is yLiI·zLiBr·(100-yz)(xLi2S·(100-x)P2S5), 70≤x≤80, 0≤y≤30, 0≤z≤30.

[0028] In the sulfide solid electrolyte of the present invention, the core and the shell are selected from the same sulfide solid electrolyte, for example, both selected from Li x MP y S z Or Li 7-x-y PS 6-x-y Cl x X y The doping elements in the sulfide solid electrolyte may be the same or different, but are preferably the same, so that the crystal structures of the core and the shell are the same. On the one hand, the core and shell with the same crystal structure have closer ionic conductivities. On the other hand, the sulfide solid electrolyte will not have core-shell separation. Therefore, not only will the ionic conductivity of the sulfide solid electrolyte not be reduced, but the air stability of the sulfide solid electrolyte can be significantly improved.

[0029] Furthermore, in the sulfide solid electrolyte of the present invention, the inner core is used as the innermost layer, and the molar amount of the doping element increases layer by layer from the innermost layer to the Nth shell layer, and the total molar amount of phosphorus and sulfur elements decreases layer by layer. For example, when N is 2, the surface of the inner core is sequentially coated with the first shell layer and the second shell layer, and the molar amount of the doping element increases layer by layer from the inner core to the second shell layer, and the total molar amount of phosphorus and sulfur elements decreases layer by layer; when N is 4, the surface of the inner core is sequentially coated with the first shell layer, the second shell layer, the third shell layer and the fourth shell layer, and the molar amount of the doping element increases layer by layer from the inner core to the fourth shell layer, and the total molar amount of phosphorus and sulfur elements decreases layer by layer.

[0030] It should be noted that when there is only one doping element, the molar amount of the doping element increases layer by layer, and when there are two or more doping elements, the total molar amount of the doping elements increases layer by layer. At this time, there is no restriction on the change rule of the molar amount of any one doping element, and it can increase layer by layer, or decrease layer by layer, or remain unchanged, or increase or decrease irregularly. Similarly, when the total molar amount of phosphorus and sulfur decreases layer by layer, there is no restriction on the change rule of the molar amount of sulfur or phosphorus.

[0031] In the sulfide solid electrolyte, the higher the molar amount of the doping element, the more obvious the improvement of the air stability of the sulfide solid electrolyte, but the more obvious the reduction of the ionic conductivity. In this regard, in the sulfide solid electrolyte of the present invention, the molar amount of the doping element is arranged in a layer-by-layer increasing manner from the innermost layer to the Nth shell layer, while ensuring that the ionic conductivity of the sulfide solid electrolyte is not significantly reduced, the air stability of the sulfide solid electrolyte can be significantly improved.

[0032] Preferably, the molar amount of any doping element in the core is 0 to 0.01, and the molar amount of any doping element in the Nth shell is 0.003 to 0.25; further, in the direction from the innermost layer to the Nth shell, the difference in the total molar amount of doping elements in two adjacent layers is preferably 0.001 to 0.25. Such a setting is more conducive to improving the air stability of the sulfide solid electrolyte without reducing the ionic conductivity of the sulfide solid electrolyte.

[0033] Preferably, in the direction from the innermost layer to the Nth shell layer, the mass of the outer layer in the two adjacent layers is less than or equal to the mass of the inner layer, and further, the mass ratio of the outer layer to the inner layer in the two adjacent layers is 1:1 to 0.1:1. It can be understood that in the two adjacent layers, the outer layer is coated on the surface of the inner layer. For example, when N is 2, in the direction from the innermost layer to the second shell layer, the mass ratio of the first shell layer to the inner core is 1:1 to 0.1:1, and the mass ratio of the second shell layer to the first shell layer is 1:1 to 0.1:1; when N is 4, in the direction from the innermost layer to the fourth shell layer, the mass ratio of the first shell layer to the inner core is 1:1 to 0.1:1, the mass ratio of the second shell layer to the first shell layer is 1:1 to 0.1:1, the mass ratio of the third shell layer to the second shell layer is 1:1 to 0.1:1, and the mass ratio of the fourth shell layer to the third shell layer is 1:1 to 0.1:1. Such a configuration is also more conducive to improving the air stability of the sulfide solid electrolyte without reducing the ionic conductivity of the sulfide solid electrolyte.

[0034] Therefore, the modification method of the present invention not only does not reduce the ionic conductivity of the sulfide solid electrolyte, but also can significantly improve the air stability of the sulfide solid electrolyte. After testing, the sulfide solid electrolyte of the present invention is exposed at a dew point of -50°C, the amount of H2S generated is significantly reduced, the structural damage of the sulfide solid electrolyte is reduced, and the ionic conductivity retention rate after exposure is high.

[0035] In a specific embodiment, N is 4, and the sulfide solid electrolyte includes a core and a first shell, a second shell, a third shell, and a fourth shell sequentially coated on the surface of the core. The molar amount of the doping element in the core is a, 0≤a<0.01, the molar amount of the doping element in the first shell is b, 0.01≤b<0.03, the molar amount of the doping element in the second shell is c, 0.03≤c<0.05, the molar amount of the doping element in the third shell is d, 0.05≤d<0.1, and the molar amount of the doping element in the fourth shell is e, 0.1≤e<0.25; in the sulfide solid electrolyte, the mass fraction of the core is 50% to 70%, the mass fraction of the first shell is 10% to 30%, the mass fraction of the second shell is 5% to 15%, the mass fraction of the third shell is 3% to 10%, and the mass fraction of the fourth shell is 1% to 5%. With such a configuration, the sulfide solid electrolyte has higher ionic conductivity and air stability.

[0036] The present invention also provides a method for preparing the sulfide solid electrolyte, comprising the following steps:

[0037] In a protective atmosphere, the raw materials are mixed and sintered by dry mixing or wet mixing according to the composition of the core to obtain the core;

[0038] In a protective atmosphere, raw materials are added in sequence according to the composition and quantity of the shells, and mixing and sintering are continued to obtain a sulfide solid electrolyte.

[0039] For example, when N is 2, the raw materials are added to the inner core, and mixing and sintering are continued to form a first shell layer coated on the inner core, and then the raw materials are continued to be added for mixing and sintering, and the second shell layer is coated on the first shell layer to obtain a sulfide solid electrolyte; when N is 4, the raw materials are added to the inner core, and mixing and sintering are continued to form a first shell layer coated on the inner core, and then the raw materials are continued to be added for mixing and sintering, and the second shell layer is coated on the first shell layer to form a second shell layer, and then the raw materials are continued to be added for mixing and sintering, and the second shell layer is coated to form a third shell layer, and then the raw materials are continued to be added for mixing and sintering, and the fourth shell layer is coated on the third shell layer to obtain a sulfide solid electrolyte.

[0040] Preferably, the particle size of the raw materials is 5 μm to 100 mm, so that the raw materials can be mixed better and the solid-solid reaction can be more complete.

[0041] Preferably, during wet mixing, the solvent is selected from at least one of toluene, xylene, heptane, carbon tetrachloride, isobutyl isobutyrate, tetrahydrofuran, acetonitrile, n-butanol, isopropanol, and ethanol, and the drying temperature after wet mixing is 60° C. to 150° C., and the drying time is 1 h to 18 h.

[0042] Preferably, in the preparation method, the inner core and the N-1th shell layer are both sintered at low temperatures, and the Nth shell layer is sintered at high temperatures, wherein the low temperature sintering temperature is 280°C to 350°C, the time is 1h to 12h, and the high temperature sintering temperature is 400°C to 600°C, the time is 1h to 30h.

[0043] Preferably, the protective atmosphere is selected from at least one of inert atmospheres such as nitrogen or argon.

[0044] Therefore, the present invention can prepare the sulfide solid electrolyte through multi-step mixing and sintering, the preparation method is simple and suitable for industrial production.

[0045] The present invention also provides an all-solid-state battery, which uses the sulfide solid electrolyte.

[0046] Since the air stability of the sulfide solid electrolyte of the present invention is improved, the electrochemical performance of the all-solid-state battery can be significantly improved by assembling the all-solid-state battery using the sulfide solid electrolyte of the present invention. Moreover, the all-solid-state battery does not need to be assembled in a protective atmosphere.

[0047] The present invention also provides an electrical device, which is a vehicle, a mobile electronic device, etc., and the electrical device uses the all-solid-state battery.

[0048] Hereinafter, the sulfide solid electrolyte and its preparation method, all-solid-state battery and electrical equipment will be further described through the following specific examples.

[0049] Example 1

[0050] In a nitrogen atmosphere, 0.79 g of LiCl, 2.14 g of Li2S, and 2.07 g of P2S5 were weighed into a 100 mL ball mill and ball milled at 600 rpm for 4 h to allow the raw materials to be fully mixed and reacted. They were then sintered at 290 °C for 2 h to form an inner core, which was recorded as the first product.

[0051] In a nitrogen atmosphere, 0.32 g of LiCl, 0.86 g of Li2S, 0.82 g of P2S5, and 0.0013 g of B2O3 were ball-milled for 1 h and then added to the first product. The ball-milling was continued for 2 h, and then sintered at 300 °C for 2 h to form the first shell layer on the inner core, which was recorded as the second product.

[0052] In a nitrogen atmosphere, 0.19 g of LiCl, 0.52 g of Li2S, 0.49 g of P2S5, and 0.0016 g of B2O3 were ball-milled for 1 h and then added to the second product. The ball-milling was continued for 2 h, and then sintered at 320°C for 1 h to form a second shell layer on the first shell layer, which was recorded as the third product.

[0053] In a nitrogen atmosphere, 0.13 g of LiCl, 0.35 g of Li2S, 0.32 g of P2S5, and 0.0031 g of B2O3 were ball-milled for 4 hours and then added to the third product. The ball-milling was continued for 2 hours, and then sintered at 350°C for 1 hour to form a third shell layer on the second shell layer, which was recorded as the fourth product.

[0054] In a nitrogen atmosphere, 0.079 g of LiCl, 0.22 g of Li2S, 0.20 g of P2S5, and 0.0033 g of B2O3 were ball-milled for 2 h and then added to the fourth product. The ball-milling was continued for 5 h, and then sintered at 350°C for 5 h to form a fourth shell layer on the third shell layer, which was recorded as the fifth product.

[0055] In a nitrogen atmosphere, 0.080 g of LiCl, 0.23 g of Li2S, 0.19 g of P2S5, and 0.0066 g of B2O3 were ball-milled for 4 h and then added to the fifth product. The ball-milling was continued for 2 h, and then sintered at 550 ° C for 8 h. The fifth shell layer was coated on the fourth shell layer to obtain a B / O gradient-doped sulfide solid electrolyte, whose composition is shown in Table 1.

[0056] Table 1

[0057] Chemical Expression Molar amount of P and S Molar amounts of B and O Mass(g) Kernel <![CDATA[Li6PS5Cl 1.0 ]]> 6 0 5 First Shell <![CDATA[Li 6.01 P 0.995 B 0.005 S 4.9925 O 0.0075 Cl 1.0 ]]> 5.9875 0.0125 2 Second Shell <![CDATA[Li 6.02 P 0.99 B 0.01 S 4.985 O 0.015 Cl 1.0 ]]> 5.975 0.025 1.2 The third shell <![CDATA[Li 6.06 P 0.97 B 0.03 S 4.955 O 0.045 Cl 1.0 ]]> 5.925 0.075 0.8 The fourth shell <![CDATA[Li 6.1 P 0.95 B 0.05 S 4.925 O 0.075 Cl 1.0 ]]> 5.875 0.125 0.5 The fifth shell <![CDATA[Li 6.2 P 0.9 B 0.1 S 4.85 O 0.15 Cl 1.0 ]]> 5.75 0.25 0.5

[0058] Example 2

[0059] In a nitrogen atmosphere, 1.01 g of LiCl, 2.63 g of P2S5, 2.09 g of Li2S, 1.24 g of LiBr, and 0.028 g of Bi2O3 were weighed into a 100 mL ball mill and ball milled at 550 rpm for 3 h to allow the raw materials to fully mix and react. They were then sintered at 280 °C for 1 h to form an inner core, which was recorded as the first product.

[0060] In a nitrogen atmosphere, 0.29 g of LiCl, 0.75 g of P2S5, 0.60 g of Li2S, 0.35 g of LiBr, and 0.016 g of Bi2O3 were ball-milled for 2 h and then added to the first product. The ball-milling was continued for 1 h, and then sintered at 290 ° C for 1 h to form the first shell layer on the inner core, which was recorded as the second product.

[0061] In a nitrogen atmosphere, 0.071 g of LiCl, 0.18 g of P2S5, 0.15 g of Li2S, 0.087 g of LiBr, and 0.012 g of Bi2O3 were ball-milled for 3 h and then added to the second product. The ball-milling was continued for 1 h, and then sintered at 300 ° C for 1 h to form a second shell layer on the first shell layer, which was recorded as the third product.

[0062] In a nitrogen atmosphere, 0.042 g of LiCl, 0.11 g of P2S5, 0.089 g of Li2S, 0.052 g of LiBr, and 0.012 g of Bi2O3 were ball-milled for 2 h and then added to the third product. The ball-milling was continued for 1 h, and then sintered at 320°C for 1 h to form a third shell layer on the second shell layer, which was recorded as the fourth product.

[0063] In a nitrogen atmosphere, 0.027 g of LiCl, 0.064 g of P2S5, 0.060 g of Li2S, 0.033 g of LiBr, and 0.015 g of Bi2O3 were ball-milled for 2 h and then added to the fourth product. The ball-milling was continued for 5 h, and then sintered at 470 ° C for 24 h. The fourth shell layer was coated on the third shell layer to obtain a Bi / O gradient-doped sulfide solid electrolyte, whose composition is shown in Table 2.

[0064] Table 2

[0065]

[0066] Example 3

[0067] In a nitrogen atmosphere, using xylene as a solvent, 1.42 g of LiCl, 2.49 g of P2S5, 2.07 g of Li2S, 0.011 g of Sb2S3, 0.00067 g of Li2O, and 0.0058 g of LiF were weighed and stirred for 2 h, first dried at 80 ° C for 6 h, and then sintered at 290 ° C for 1 h to form an inner core, recorded as the first product.

[0068] In a nitrogen atmosphere, 0.59 g of LiCl, 1.02 g of P2S5, 0.86 g of Li2S, 0.019 g of Sb2S3, 0.00056 g of Li2O, and 0.0024 g of LiF were dispersed in xylene, stirred for 2 h, and then added to the first product. Stirring was continued for 1 h, first dried at 90 ° C for 5 h, and then sintered at 300 ° C for 1 h to form a first shell layer on the inner core, which was recorded as the second product.

[0069] In a nitrogen atmosphere, 0.23 g of LiCl, 0.39 g of P2S5, 0.35 g of Li2S, 0.025 g of Sb2S3, 0.00033 g of Li2O, and 0.0096 g of LiF were dispersed in xylene, stirred for 2 h, and then added to the second product, and continued to stir for 1 h. First, it was dried at 100 ° C for 4 h, and then sintered at 310 ° C for 1 h to form a second shell layer on the first shell layer, which was recorded as the third product.

[0070] In a nitrogen atmosphere, 0.12 g of LiCl, 0.19 g of P2S5, 0.17 g of Li2S, 0.019 g of Sb2S3, 0.00022 g of Li2O, and 0.00048 g of LiF were dispersed in xylene, stirred for 2 h, and then added to the third product, and continued to stir for 1 h. The mixture was first dried at 110 ° C for 3 h, and then sintered at 500 ° C for 12 h. The third shell layer was coated on the second shell layer to obtain a Sb / O gradient-doped sulfide solid electrolyte, whose composition is shown in Table 3.

[0071] Table 3

[0072]

[0073] Example 4

[0074] In a nitrogen atmosphere, 0.53 g of LiCl, 2.32 g of P2S5, 1.83 g of Li2S, 1.82 g of LiBr, and 0.0058 g of SeO2 were weighed into a 100 mL ball mill and ball milled at 600 rpm for 4 h to allow the raw materials to be fully mixed and reacted. They were then sintered at 290 °C for 2 h to form an inner core, which was recorded as the first product.

[0075] In a nitrogen atmosphere, 0.20 g of LiCl, 0.88 g of P2S5, 0.70 g of Li2S, 0.70 g of LiBr, and 0.011 g of SeO2 were ball-milled for 1 h and then added to the first product. The ball-milling was continued for 2 h, and then sintered at 300 °C for 2 h to form the first shell layer on the inner core, which was recorded as the second product.

[0076] In a nitrogen atmosphere, 0.082 g of LiCl, 0.34 g of P2S5, 0.28 g of Li2S, 0.28 g of LiBr, and 0.012 g of SeO2 were ball-milled for 1 h and then added to the second product. The ball-milling was continued for 5 h, and then sintered at 480 ° C for 20 h to form a second shell layer on the first shell layer to obtain a Se / O gradient-doped sulfide solid electrolyte, whose composition is shown in Table 4.

[0077] Table 4

[0078]

[0079] Comparative Example 1

[0080] In a nitrogen atmosphere, 1.58 g of LiCl, 4.10 g of P2S5, 4.31 g of Li2S, and 0.016 g of B2O3 were weighed into a 100 mL ball mill and milled at 600 rpm for 12 h to fully mix the raw materials. Then, the raw materials were sintered at 550 ° C for 8 h to obtain a B / O-doped sulfide solid electrolyte with the chemical formula of Li 6.0243 P 0.9878 B 0.0122 S 4.9818 O 0.0182 Cl 1.0 .

[0081] Comparative Example 2

[0082] In a nitrogen atmosphere, 1.44 g of LiCl, 3.73 g of P2S5, 1.98 g of Li2S, 1.77 g of LiBr, and 0.082 g of Bi2O3 were weighed into a 100 mL ball mill and milled at 550 rpm for 20 h to fully mix the raw materials. The materials were then sintered at 470 °C for 24 h to obtain a Bi / O-doped sulfide solid electrolyte with the chemical formula Li 5.4226 P 0.9896 Bi 0.0104 S 4.3854 O 0.0155 Cl 1.0 Br 0.6 .

[0083] Comparative Example 3

[0084] In a nitrogen atmosphere, xylene was used as a solvent, 2.36 g of LiCl, 4.10 g of P2S5, 3.45 g of Li2S, 0.074 g of Sb2S3, 0.0018 g of Li2O, and 0.0097 g of LiF were weighed and stirred for 2 h, first dried at 110 ° C for 6 h, and then sintered at 500 ° C for 12 h to obtain a Sb / O-doped sulfide solid electrolyte, whose chemical formula is Li 5.5234 P 0.9883 Sb 0.0117 S 2.498 4O 0.0016 Cl 1.49 F 0.01 .

[0085] Comparative Example 4

[0086] In a nitrogen atmosphere, 0.82 g of LiCl, 3.55 g of P2S5, 2.81 g of Li2S, 2.79 g of LiBr, and 0.029 g of SeO2 were weighed into a 100 mL ball mill and milled at 600 rpm for 15 h to fully mix the raw materials. Then, the raw materials were sintered at 480 ° C for 20 h to obtain a Se / O-doped sulfide solid electrolyte with the chemical formula of Li 5.4081 P 0.9919 S 4.3838 S e0.0081 O 0.0162 Cl 0.6 Br 1.0 .

[0087] The sulfide solid electrolytes obtained in the examples and comparative examples were subjected to air stability tests in a dry room with a dew point of -50°C. The test process is as follows:

[0088] After the sulfide solid electrolyte was exposed to a dry room at a dew point of -50°C for different times, 150 mg of powder was weighed and placed in a battery mold (inner diameter 10 mm), a pressure of 100 MPa was applied, and the AC impedance was tested using an electrochemical workstation, with an applied voltage of 20 mV in the frequency range of 1 Hz to 1 MHz. The ionic conductivity of the sulfide solid electrolyte after different exposure times was calculated, and the test results are shown in Table 5.

[0089] Table 5

[0090]

[0091] It can be seen from Table 5 that the modification method of the sulfide solid electrolyte of the present invention not only does not reduce its ionic conductivity, but also can significantly improve its air stability test results. The sulfide solid electrolyte still has a high ionic conductivity after exposure for 2 hours.

[0092] The sulfide solid electrolyte after exposure for 30 minutes in the embodiment and the comparative example was added to the ternary composite positive electrode to prepare the positive electrode layer. The sulfide solid electrolyte after exposure for 30 minutes was used as the electrolyte layer, and metallic lithium was used as the negative electrode. The all-solid-state battery was assembled and then the performance test was carried out. The test process is as follows, and the test results are shown in Table 6.

[0093] First charge and discharge test: All-solid-state battery at 25°C, 0.1C constant current charge and discharge test for 1 cycle, voltage range 2.7-4.3V.

[0094] Rate test: The all-solid-state battery is charged and discharged at 0.2C, 0.5C, and 2C constant currents for 5 cycles at 25°C, with a voltage range of 2.7-4.3V.

[0095] Long cycle test: The all-solid-state battery is charged and discharged for 100 cycles at 0.1C constant current at 25°C, with a voltage range of 2.7-4.3V.

[0096] Table 6

[0097]

[0098] It can be seen from Table 6 that the first discharge specific capacity, coulombic efficiency, capacity retention rate and rate performance of the all-solid-state batteries assembled using the sulfide solid electrolytes of Examples 1-4 are all improved accordingly.

[0099] In summary, the present invention not only does not reduce the ionic conductivity of the sulfide solid electrolyte, but also can significantly improve the air stability of the sulfide solid electrolyte. The use of the sulfide solid electrolyte of the present invention to assemble an all-solid-state battery can significantly improve the electrochemical performance of the all-solid-state battery. Moreover, the assembly of the all-solid-state battery does not need to be carried out in a protective atmosphere.

[0100] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0101] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A sulfide solid electrolyte, characterized in that: The sulfide solid electrolyte includes an inner core and N shell layers sequentially coated on the surface of the inner core, N is an integer greater than or equal to 2, and both the inner core and the shell layers are sulfide solid electrolytes doped with doping elements, wherein the inner core and the shell layers have the same crystal structure, and with the inner core as the innermost layer, from the innermost layer to the Nth shell layer, the molar amount of the doping element increases layer by layer, and the total molar amount of phosphorus and sulfur decreases layer by layer.

2. The sulfide solid electrolyte according to claim 1, characterized in that The sulfide solid electrolyte also satisfies at least one of the following conditions: (1) The molar amount of any doping element in the core is 0 to 0.01, and the molar amount of any doping element in the Nth shell is 0.003 to 0.25; (2) In the direction from the innermost layer to the Nth shell, the mass of the outer layer in two adjacent layers is less than or equal to the mass of the inner layer.

3. The sulfide solid electrolyte according to claim 2, characterized in that: The sulfide solid electrolyte also satisfies at least one of the following conditions: (1) From the innermost layer to the Nth shell, the difference in the total molar amount of the doping elements in two adjacent layers is 0.001 to 0.25; (2) In the direction from the innermost layer to the Nth shell, the mass ratio of the outer layer to the inner layer in two adjacent layers is 1:1 to 0.1:

1.

4. The sulfide solid electrolyte according to claim 1, characterized in that The doping element is selected from at least one of B, O, Sb, Sn, Bi, Se, Zn, Fe, Cu, Ga, Zr, Y, Ta, W, In, Mo, Al, and N.

5. The sulfide solid electrolyte according to claim 4, characterized in that: The doping element is selected from at least one of O, Sb, Sn, Bi, Se, In, and N.

6. The sulfide solid electrolyte according to any one of claims 1 to 5, characterized in that N is 4, and the sulfide solid electrolyte includes an inner core and a first shell layer, a second shell layer, a third shell layer and a fourth shell layer sequentially coated on the surface of the inner core.

7. The sulfide solid electrolyte according to claim 6, characterized in that The sulfide solid electrolyte satisfies at least one of the following conditions: (1) the molar amount of any doping element in the core is a, 0≤a<0.01, the molar amount of any doping element in the first shell is b, 0.01≤b<0.03, the molar amount of any doping element in the second shell is c, 0.03≤c<0.05, the molar amount of any doping element in the third shell is d, 0.05≤d<0.1, and the molar amount of any doping element in the fourth shell is e, 0.1≤e<0.25; (2) In the sulfide solid electrolyte, the mass fraction of the core is 50% to 70%, the mass fraction of the first shell is 10% to 30%, the mass fraction of the second shell is 5% to 15%, the mass fraction of the third shell is 3% to 10%, and the mass fraction of the fourth shell is 1% to 5%.

8. A method for preparing a sulfide solid electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: In a protective atmosphere, the raw materials are mixed and sintered by dry mixing or wet mixing according to the composition of the core to obtain the core; In a protective atmosphere, raw materials are added in sequence according to the composition and quantity of the shell layers, and mixing and sintering are continued to obtain a sulfide solid electrolyte.

9. An all-solid-state battery, characterized in that: The all-solid-state battery uses the sulfide solid electrolyte according to any one of claims 1 to 7.

10. An electrical device, characterized in that: The electrical equipment uses the all-solid-state battery as claimed in claim 9.

Citation Information

Cited By

  • Preparation method and application of niobium pentoxide doped sulfide solid electrolyte

    CN120637615A

  • Preparation method of niobium pentoxide doped sulfide solid electrolyte and application thereof

    CN120637615B